Characterisation of ventricular premature beats during exercise testing in masters athletes. (14th October 2021) - Duncan, E; Fyyaz, S; Papatheodorou, S; Merghani, A; Papadakis, M; Sharma, S
Abstract: Background: Exercise induced ventricular premature beats (VPBs) are associated with an adverse outcome in patients with cardiac disease and the general population. The incidence and significance of exercise induced VPBs in masters athletes remains unknown. Methods: 237 masters athletes (54.6±8 years of age, 42% male) and 50 controls of similar age and sex were assessed with a 12-lead ECG, echocardiogram, cardiopulmonary exercise test, 24-hour holter, cardiovascular magnetic resonance imaging and a CT coronary angiogram. Athletes had participated in endurance exercise for a meanof 32±12 years. Results: Athletes achieved a higher VO2 max (43.2 ml/min/kg vs 28 ml/min/kg) compared with controls and on average weighed 12kg less (63kg vs 75kg). VPBs were common in master athletes during exercise but are no more common than in age matched sedentary controls (39.3% vs 33.3% >1 VPB, and 8.9% vs 5.9% complex or frequent VPBs). There were no sex differences in terms of VPB number (40% vs 39%) or complex morphology (10% vs 8%) between male and female athletes. Athletes demonstrating complex ectopy during ETT had similar age (54.8±9 and 54.6±8), years of competition (34±9 and 32±12), VO2 max (40±6 and 43±7ml/min/kg), left ventricular mass (142±36g and 148±35g), end diastolic volume (160±35ml and 157±32ml) and incidence of late gadolinium enhancement (14% and 10%) compared with athletes who did not reveal complex VPBs. Conclusion: VPBs are common during exercise testing in both masters athletes and sedentary age matched controls. Exercise-induced complex ectopy in an asymptomatic, low risk masters athlete represents a poor marker of significant structural heart disease. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Cardiac Risk in the Young